Proton-capture Reaction Cross Sections on the Sr Isotopes Relevant to the p-process Nucleosynthesis - Galanopoulos, S.; Harissopulos, S.; Hammer, J. W.; Kunz, R.; Demetriou, P. (HNPS Advances in Nuclear Physics, 2020)
Proton-capture reaction cross sections on the 86,87,88Sr isotopes have been determined at energies from 1.4 to 5 MeV by measuring γ-angular distributions at the 4 MV single-ended Dynamitron accelerator of the University of Stuttgart as well as at the 5 MV VdG Tandem accelerator of NCSR "Demokritos", Athens. In the former case an array of 4 HPGe detectors with relative efficiency εr≈100%, each shielded with BGO crystals, were used. In the case of the measurements carried out at "Demokritos" we used only one HPGe detector (εr≈80%) with no BGO shield. Cross sections ranging from 0.5 μb to 5 mb as well as the relevant S factors were obtained. The data were compared with statistical model calculations using the code MOST. In the calculations, various combinations of microscopic and phe- nomenological models of the nucleon-Nucleus Optical Model Potentials (OMP) and Nuclear Level Densities (NLD) were used and a good agreement between the data and theoretical predictions was found.